192. A Hematology/Oncology Unit-Specific Antibiogram Emphasizes the Need for Intensified Local Stewardship. (31st December 2020) - Bartash, Rachel; McCort, Margaret E; Cowman, Kelsie; Orner, Erika; Szymczak, Wendy; Nori, Priya; Nori, Priya
Abstract: Background: Antibiograms are important stewardship tools for empiric antibiotic prescribing. Appropriate therapy is particularly important in patients with hematologic malignancies and bone marrow transplants being treated for febrile neutropenia. These patients are at high risk for multi-drug resistance based on extensive prior antibiotic and hospital exposures, and therefore, hospital-wide antibiograms may not reliably reflect resistance patterns for this population. We created a unit-specific antibiogram for a closed hematology/oncology unit and hypothesized there would be decreased antibiotic susceptibilities compared to the hospital-wide antibiogram. Methods: All positive cultures with antimicrobial susceptibilities on a closed 32-bed hematology-oncology unit from 7/2016-6/2019 were obtained from the microbiology laboratory. Based on recommendations by the Clinical and Laboratory Standards Institute (CLSI), only organisms with > 30 isolates were included in antibiogram analysis. Susceptibilities were compared to those reported in our hospital-wide antibiograms from the same time period using Fisher's exact test. Results: Two organisms met CLSI criteria: Escherichia coli (n=83) and Klebsiella pneumoniae (n=31). Unit Escherichia coli isolates were significantly more resistant to almost all commonly tested antibiotics (Table 1). Klebsiella pneumoniae unit susceptibilities were significantly lower for many antibiotics, including aztreonam, ceftriaxone, cefepime, levofloxacin, piperacillin-tazobactam and tobramycin (Table 1). Table 1: Percentage of Escherichia coli and Klebsiella pneumoniae isolates susceptible to reported antibiotic agents Conclusion: Our hematology-oncology antibiogram showed significantly lower antibiotic susceptibilities in Escherichia Coli and Klebsiella pneumoniae compared with the hospital-wide antibiogram. These findings can help guide prescribers toward appropriate broad-spectrum empiric therapy. Additionally, results suggest a need for intensified stewardship measures to prevent multi-drug resistance in this population. Disclosures: All Authors : No reported disclosures